2022
DOI: 10.1021/acs.nanolett.2c02418
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Deformation and Giant Electronic Band Modulation in Long-Wavelength WS2 Moiré Superlattices

Abstract: As a lattice interference effect, moirésuperlattices feature a magnification effect that they respond sensitively to both the extrinsic mechanical perturbations and intrinsic atomic reconstructions. Here, using scanning tunneling microscopy and spectroscopy, we observe that long-wavelength WS 2 superlattices are reconstructed into various moirémorphologies, ranging from regular hexagons to heavily deformed ones. We show that a dedicated interplay between the extrinsic nonuniform heterostrain and the intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…40 Since the important physics is localized to the bubble edge, we approximate the bubble region by a 2D inclusion in monolayer MoSe 2 (large enough to isolate the two interfaces required by periodic boundary conditions), with a downward shift of the conduction band in the bubble region, as well as a background doping, that both increase with strain. 41 The strain is assumed to be slightly larger at the edge of the bubble region. The DOS is calculated assuming a 2D parabolic dispersion in the direction parallel to the inclusion above the conduction-band minimum and below the valence band maximum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Since the important physics is localized to the bubble edge, we approximate the bubble region by a 2D inclusion in monolayer MoSe 2 (large enough to isolate the two interfaces required by periodic boundary conditions), with a downward shift of the conduction band in the bubble region, as well as a background doping, that both increase with strain. 41 The strain is assumed to be slightly larger at the edge of the bubble region. The DOS is calculated assuming a 2D parabolic dispersion in the direction parallel to the inclusion above the conduction-band minimum and below the valence band maximum.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we take band parameters for MoSe 2 from ref and electromechanical parameters from ref . Since the important physics is localized to the bubble edge, we approximate the bubble region by a 2D inclusion in monolayer MoSe 2 (large enough to isolate the two interfaces required by periodic boundary conditions) with a downward shift of the conduction band in the bubble region as well as a background doping, which both increase with strain . The strain is assumed to be slightly larger at the edge of the bubble region.…”
mentioning
confidence: 99%
“…Although the 1H phase shows an energy gap, the “V” shape manifests the metallic 1T′ phase at the temperature of liquid nitrogen. In addition to structural phases, electronic phases can be studied using STM, such as the direct visualization of moiré potentials or CDWs in WSe 2 /MoSe 2 , WS 2 /WSe 2 , restacked WS 2 , 1T TaSe 2 , and 1T VSe 2 . For example, at 5 K, a 4 × 4 superstructure was observed in 1T VSe 2 , and its periodicity was confirmed by the Fourier-transform (FT) images in Figures (g) and (h) .…”
Section: Structure Characterizationmentioning
confidence: 83%
“…For Group VIIB, ReS 2 and ReSe 2 are semiconducting and have highly anisotropic symmetry. , Structural phases are periodically related to the d -band electrons of the transition metal. , One TMD nanosheet polytype could be directly grown using chemical vapor deposition (CVD), , solid state reaction, vdW epitaxy, ,, atomic layer deposition (ALD), or wet chemical synthesis, , and transformed from another polytype, ,, as shown in Figure . To elucidate TMD structures, various characterization tools have been studied and developed, including optical microscopy, , atomic force microscopy (AFM), , Raman spectroscopy, transmission electron microscopy (TEM), photoluminescence (PL) spectroscopy, scanning tunneling microscopy/spectroscopy (STM/STS), and angle-resolved photoemission spectroscopy (ARPES). The diversity of chemical compositions and structural phases is a striking feature of TMDs, and the rapid development of TMD synthesis and structural characterization methods enables a wide range of TMD applications in, for example, electronic devices, , biosensors, photodetectors, laser emitters, and energy storage. …”
Section: Introductionmentioning
confidence: 99%
“…From the experimental perspective, we have exploited the native biaxial heterostrain in intercalated bilayer graphene on SiC that is certainly stabilized by non intercalated regions. Experiments in trilayer graphene [50] and WS 2 [51] with similar morphology indicate that the atomic swirl also occurs in other van de Waals stacks under appropriate conditions and this is supported by very recent calculations [52] in MoX 2 /WX 2 (TMDs with X = S or Se). A more systematic study will require to control biaxial heterostrain as was recently demonstrated in ref.…”
Section: Discussionmentioning
confidence: 99%